Answer:
( x + 3 )² - 27
Step-by-step explanation:
x² + 6x = 18
→ Minus 18 from both sides to get a quadratic equation
x² + 6x - 18
⇒Completed square from is ( x + a )² + b
⇒The value of 'a' will always be half the 'b' value in the equation
ax² + bx + c
→( x + 3 )² + b
Expand out the equation to find 'b'
x² + 6x + 9
We have do something to get from 9 to - 18 which -27
So the answer is ( x + 3 )² -27
I don't know what c you are talking about because there is no picture
Answer:
1 neither
2 supplementary
3 supplementary
Step-by-step explanation: